Translasi Representasi Matematis Siswa SMP dalam Menyelesaikan Masalah Ditinjau Berdasarkan Kemampuan Matematika - Erni Agustina Sari; Susanah Susanah (Program Studi S1 Matematika UNESA, 2023)
This study aims to analyze the translation of mathematical representations of verbal problems. Three grade VIII students of junior high school were selected as subjects based on the results of the task of translation ability of mathematical representation. Assignments in the form of algebraic problems were given to subjects and then task-based interviews were carried out. The translation indicator of the mathematical representation used to analyze the results of problem solving and interviews consists of four stages, namely unpacking the source, preliminary coordinator, constructing the target, and determining equivalence. The results of this study indicate that high ability students solve problems well. At the unpacking stage, the source is translated using verbal representations, coordinating understanding is translated using visual and symbolic representations, constructing the target goals is translated using symbolic representations, and in determining suitability is translated using verbal representations. Students with ability are solving problems well but there are still errors at the stage of coordinating initial understanding and constructing target goals. Students disassemble the source translated using verbal and symbolic representations, coordinate the initial understanding translated using visual and symbolic representations, construct the target goals translated using symbolic representations, and determine the suitability of being translated using verbal representations. Low ability students cannot continue solving problems. As for the translation of the subject's representation in disassembling the source is translated using verbal representations, coordinating the initial understanding is translated using visual and symbolic representations, not constructing the target goals, and using verbal representations when determining the suitability of being translated.